Wujud Budaya dan Nilai Pendidikan dalam Adat Berontang pada Masyarakat Desa Semadin Kecamatan Nanga Pinoh Kabupaten Melawi (Kajian Antropologi Sastra) - Krisna Natalia; Rini Agustina; Lizawati Lizawati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
This research aims to describe the cultural forms and educational values within the Berontang custom practiced by the community of Semadin Village, Nanga Pinoh District, Melawi Regency. Berontang is a traditional communal dining ceremony rooted in the Dayak Kebahant culture, rich in cultural significance and educational values. The study employs a qualitative approach with descriptive methods. Data collection techniques include interviews, direct observation, and documentation. Data were analyzed using an interactive analysis model and validated through source and theoretical triangulation. The findings reveal that cultural forms in the Berontang tradition are reflected in communal work activities and the artifacts used in the ceremony. The educational values found include social values such as mutual cooperation and solidarity. This research not only documents a fading local tradition but also highlights the embedded educational values, making it a useful reference for learning, particularly for the hikayat text in senior high school curricula. These findings are expected to contribute to the preservation of local culture and strengthen community identity and character through culture-based education.